2014
DOI: 10.1007/s10548-014-0415-1
|View full text |Cite
|
Sign up to set email alerts
|

Automated Hippocampal Subfield Measures as Predictors of Conversion from Mild Cognitive Impairment to Alzheimer’s Disease in Two Independent Cohorts

Abstract: Previous studies have shown that hippocampal subfields may be differentially affected by Alzheimer’s disease (AD). This study used an automated analysis technique and two large cohorts to (1) investigate patterns of subfield volume loss in mild cognitive impairment (MCI) and AD, (2) determine the pattern of subfield volume loss due to age, gender, education, APOE ε4 genotype, and neuropsychological test scores, (3) compare combined subfield volumes to hippocampal volume alone at discriminating between AD and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 56 publications
(85 reference statements)
8
64
1
Order By: Relevance
“…There were significant positive correlations between the neuropsychological tests, like MocA, and the subfield volumes. These results were also consistent with previous studies [17, 23, 42] and indicated that atrophy may be associated with cognitive impairment. All of these results confirmed that the Chinese AD population has a quite similar atrophy pattern to the previously reported Caucasian results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There were significant positive correlations between the neuropsychological tests, like MocA, and the subfield volumes. These results were also consistent with previous studies [17, 23, 42] and indicated that atrophy may be associated with cognitive impairment. All of these results confirmed that the Chinese AD population has a quite similar atrophy pattern to the previously reported Caucasian results.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found a significant reduction in the bilateral hippocampal subfield volume in MCI patients, which replicated previous studies [3, 17, 23, 3335]. Four subfields of the hippocampus were significantly different between the MCI and NC groups (FDR corrected), indicating that atrophy of the left presubiculum/subiculum and right CA2_3 and CA4_DG volume may be a more powerful biomarker for MCI than other hippocampal subfields.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the first case, the classifier performed with 84% sensitivity and 91% specificity, and its prediction of conversion from MCI to AD at 12 months was 91% [60]. The combination of the hippocampal subfields volumes achieved an AD/HC classification accuracy of 82% and a prediction accuracy of 81% [61].…”
Section: European Adni and Addneuromedmentioning
confidence: 96%
“…Two other efforts used orthogonal partial least squares to latent structures, a multivariate analysis technique, to classify subjects with AD and HC. The classifier models involved cortical thickness measures and subcortical volumes in the first study [60] and hippocampal subfield volumes in the second study [61]. In the first case, the classifier performed with 84% sensitivity and 91% specificity, and its prediction of conversion from MCI to AD at 12 months was 91% [60].…”
Section: European Adni and Addneuromedmentioning
confidence: 99%